Una aproximación al reconocimiento de derechos a otros seres vivientes: Caso del Derecho Animal - Villanueva Aramayo, Alessandra (2019)
In the course of the last century, progress has made regarding the recognition of human rights. However, in most recent decades, the question of whether this recognition of rights should be extended to other living species has arisen. Building on this debate, it is worth wondering whether it would be possible to recognize rights in favor nonhuman animals, in Peru.This article seeks to outline the main advances made in the recognition of animal rights, starting from a historical evolution recount of the recognition of animal welfare since the 17th century, times in which animals were an object of the human environment, until the first decades of the 21st century, where animal interests begin to be legislated. Furthermore, having analyzed the similarities and differences between human beings and animals, this article presents the possible categories attributable to the latter. Lastly, it identifies the current role of animals in social practices and how their right or interest is collected by the legal system, to suggest alternatives for its regulation.